Analysis of Public Sector Financial Performance With The Value For Money Approach In Bogor Regency - Erica, Denny; Shah, Syed Muhammad Abdul Rehman; Ratiyah, Ratiyah (Universitas Ahmad Dahlan, Yogyakarta, 2025)
Financial performance is essential to ensure accountability and efLiciency in public sector organizations, especially in government. Public Sector Financial Performance requires assessment as a form of evaluation, so that Linancial performance becomes more optimal. The process of regional Linancial management consists of three stages: planning, implementation, and accountability, according to Minister of Home Affairs Regulation Number 13 of 2006 Concerning Regional Finavfc ncial Management Guidelines. The Financial Performance of the Bogor Regency Government in this study uses the Value for Money (VfM) approach with 3 (three) main factors, namely: Economic, EfLiciency, and Effectiveness of the 2014-2023 Fiscal Year. The Linancial reports produced have been in accordance with government accounting standards agreed upon by all parties involved, therefore used as a guideline to produce fair, clear, and complete Linancial reports to ensure transparency. The budget implementation report is a Linancial report that describes the future budget and budget allocation managed by the government during the reporting period. The Linancial performance of the Bogor Regency public sector is economical, with an average of 100.58%. However, efLiciency is still a concern, with an average of 99.21%, which needs more attention. The results of this analysis can be used as evaluation material for the Bogor Regency Government so that its public sector Linancial performance is more efLicient, so that the Bogor Regency Government can improve the quality of service to the community to be more optimal.